2020
DOI: 10.21203/rs.3.rs-99694/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors Impacting Intra- and Postoperative Cerebrospinal Fluid Rhinorrhea on the Endoscopic Treatment of Pituitary Adenomas: Retrospective Experience From 250 Patients

Abstract: Aim: We aimed to identify the risk factors associated with intra- and postoperative cerebrospinal fluid leakage in pituitary adenomas treated by endoscopic transsphenoidal surgery. Material and methods: A retrospective analysis of 250 pituitary adenoma cases from January 2017 to December 2019 at our hospital was conducted; all patients underwent endoscopic endonasal transsphenoidal surgeries. A univariate analysis and multivariate analysis was performed to investigate the risk factors associated with intra- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…Consistent with reports in the literature (13,18), our study showed that intraoperative CSF leak increases postoperative CSF leak rate. In this study, 107 (26.8%) patients developed intraoperative CSF leak.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with reports in the literature (13,18), our study showed that intraoperative CSF leak increases postoperative CSF leak rate. In this study, 107 (26.8%) patients developed intraoperative CSF leak.…”
Section: Discussionsupporting
confidence: 92%
“…CSF leak is one of the most common postoperative complications after EES for pituitary adenomas. According to literature reports, the incidence of CSF leak after EES for pituitary adenomas ranges from 2.6% to 12.1% (4,(11)(12)(13)(14)(15)(16)(17). In the current study, 3.5% of patients with pituitary adenomas developed cerebrospinal fluid leakage after EES.…”
Section: Discussionsupporting
confidence: 46%